Diagnosis dan Penatalaksanaan Karsinoma Tonsil - Benny Kurnia; Lily Setiani; Juniar Juniar; Safarianti Safarianti (Jurnal Kedokteran Syiah Kuala, 2021)
AbstractTonsilar carcinoma is the most common squamous cell carcinoma of the tonsils that presents as ulcerated lesions on a necrotic basis. These tumors often appear at an advanced stage and often metastasize to the lymph nodes. In recent years, head and neck malignancies due to HPV infection have increased. Other causes of carcinoma of the tonsils are smoking and alcohol abuse. The overall incidence of tonsillar carcinoma increase in the younger population, and this may be associated with an increase of human papilloma virus infection. Tonsil carcinoma varies in clinical history. In the early stages, tonsilar carcinoma are asymptomatic, but at an advanced stages patients might have complaint of a persistent sore throat, unilateral otalgia, or a sensation of mass in the throat, bleeding from the mouth, fetor oris with trismus as a sign of a local invasion. The diagnosis of tonsilar carcinoma made based on history, physical examination, clinical symptoms, and supporting examinations such as of CT scan, MRI and tumor tissue biopsy. Management of tonsilar carcinoma for stage I-II and stage III (T1-2, N1) are local and regional radiotherapy to achieve a good effect. Radiotherapy is the main treatment modality in early-stage of tonsillar carcinoma. concomitant chemotherapy and radiation therapy are the standard treatment for advanced tonsillar carcinoma currently. chemotherapy can be given before radiotherapy or as neoadjuvant, given after radiotherapy or as adjuvant, or given concurrently with radiotherapy.